West Sumatra Governor's Crisis Communication in The Air Bangis Agrarian Conflict - Arif, Adzkia; Arif, Ernita; Asmawi, Asmawi (Alfuad: Jurnal Sosial Keagamaan, 2024)
Land conversion often causes friction between the government and the community, which leads to conflict. West Pasaman is one of the districts in West Sumatra Province with the highest cases of agrarian conflict in West Sumatra. Data from the Padang City Legal Aid Institute shows that there are 25 cases of agrarian conflict in West Pasaman Regency, one of which occurred in Jorog Pigogah Patibubur. This research focuses on government crisis communication in dealing with conflict. Using the Two Ways Symmetrical Communication model, this research will analyze how the government-society narratives differ regarding the PSN Air Bangis proposal, the process of forming the narrative, and the communication strategy of the Governor of West Sumatra in managing the crisis. This research uses qualitative methods to analyze the management of narratives and conflicts between the Governor of West Sumatra, Mahyeldi Ansharullah and the Air Bangis community regarding the change in the status of forest areas that were originally cultivated by the community, to become production forest areas managed by the state. To obtain data, this research used interview and document study methods. Research shows that the crisis cannot be handled optimally because the crisis communication strategies used by the government have not been successful in managing the conflict.